144k views
0 votes
3x= 5 + 2(3 + 4x)
How to solve this?

2 Answers

2 votes

Answer:

Explanation:

Simplifying

3x = 5 + 2(3 + 4x)

3x = 5 + (3 * 2 + 4x * 2)

3x = 5 + (6 + 8x)

Combine like terms: 5 + 6 = 11

3x = 11 + 8x

Solving

3x = 11 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.

3x + -8x = 11 + 8x + -8x

Combine like terms: 3x + -8x = -5x

-5x = 11 + 8x + -8x

Combine like terms: 8x + -8x = 0

-5x = 11 + 0

-5x = 11

Divide each side by '-5'.

x = -2.2

Simplifying

x = -2.2

User TheKalpit
by
5.2k points
3 votes

Answer:

x = -11/5

Explanation:

3x = 5 + 2(3 + 4x)

~Distribute left side

3x = 5 + 6 + 8x

~Combine like terms on the left side

3x = 11 + 8x

~Subtract 8x to both sides

-5x = 11

~Divide -5 to both sides

x = -11/5

Best of Luck!

User Dawid Karabin
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.